Characterization of Fe2O3 Nanopowder Synthesized by Sol-Gel Method for Energy Storage Applications - Thi Hang, Bui (VNU Journal of Science: Mathematics - Physics; Vol 39 No 3DO - 10.25073/2588-1124/vnumap.4848, 2023)
Fe 2 O 3 nanopowder was synthesized by sol-gel method from the iron source material Fe(NO 3 ) 3 .9H 2 O and citric acid C 6 H 8 O 7 .H 2 O without any refined process. The structure and particles size of the synthesized materials were determined by X-ray diffraction and scanning electron microscopy. The obtained product is α-Fe 2 O 3 with different shapes and sizes depending on the preparation conditions. α-Fe 2 O 3 was applied as anode of iron-air battery. The cyclic voltammetry measurements showed that the size and morphology of Fe 2 O 3 particles affect the electrochemical characteristics of the electrodes. Using K 2 S as an electrolyte additive improved the electrochemical properties of mixing of Fe 2 O 3 and carbon acetylene black (Fe 2 O 3 /AB) electrodes as evidenced by increased redox reaction rate of iron, increased capacity of Fe 2 O 3 /AB electrode and reduced H 2 evolution.